HUBUNGAN KONSUMSI GULA, NATRIUM, LEMAK, DAN AKTIVITAS FISIK DENGAN KEJADIAN HIPERTENSI PADA REMAJA DI SMP NEGERI 21 TANGERANG SELATAN - Azahra Martania Jaya (2023)
Hypertension is a condition of blood pressure above normal values, this disease is not only experienced by the elderly, adults, but also by adolescents. Hypertension can be influenced by several factors such as diet and physical activity. This study aims to determine the relationship between consumption of sugar, sodium, fat, and physical activity with the incidence of hypertension in adolescents at SMP Negeri 21 Tangerang Selatan. This research is an observational analytic with a cross-sectional study design that has a sample size of 80 participants using the stratified random sampling method and was conducted from March to June 2023. The results of the bivariate test with chi-square showed that there was an association between fat consumption (p=0.001; OR=3.026) and physical activity (p=0.002; OR=4.015) with hypertension in adolescents. While sugar consumption (p=0.627) and sodium consumption (p=0.202) showed no association with hypertension in the elderly. It is expected for the community to maintain their food intake, especially in the consumption of sugar, sodium and fat and do physical activity in order to maintain normal blood pressure.